Investigations to explore interactions in (polyhydroxy solute + l-ascorbic acid + H2O) solutions at different temperatures: Calorimetric and viscometric approach. (November 2016) - Banipal, Parampaul K.; Sharma, Mousmee; Aggarwal, Neha; Banipal, Tarlok S.
Graphical abstract: Highlights: The hydrophilic-hydrophilic interactions predominate at low temperatures. Enthalpy change for polyol is less exothermic than its parent saccharide. Δdil C o p, 2, m values suggest structural increase in presence ofl -ascorbic acid. Solutes act as kosmotropes inl -ascorbic acid(aq) solutions as indicated by d B /d T . Abstract: Isothermal titration micro-calorimeter has been used to measure the enthalpy change ( q ) of polyhydroxy solutes [(+)-d -xylose, xylitol, (+)-d -glucose, 2-deoxy-d -glucose, (+)-methyl-α-d -glucopyranoside, and (+)-maltose monohydrate] in water and in (0.05, 0.15, and 0.25) mol·kg −1 l -ascorbic acid(aq) solutions at (288.15, 298.15, 308.15, and 318.15) K. Limiting enthalpies of dilution (Δdil H °) of these solutes were calculated from heat evolved/absorbed during calorimetric experiments. Further thermodynamic quantities such as limiting enthalpies of dilution of transfer (Δtr Δdil H °), change in heat capacity (Δdil C o p, 2, m ), and pair ( h AB ) and triplet ( h ABB ) enthalpic interaction coefficients were also calculated and used to explore the nature of interactions of solutes with cosolute (l -ascorbic acid). The Jones-Dole viscosity B -coefficients for (+)-d -xylose, xylitol, (+)-d -galactose, galactitol, (+)-d -glucose, 2-deoxy-d -glucose, (+)-methyl-α-d -glucopyranoside, and (+)-maltose monohydrate in water and in (0.05, 0.15, 0.25, and 0.35) mol·kg −1 l -ascorbic acid(aq) solutions have been determined from viscosity ( η ) data measured over temperature range (288.15–318.15) K and at pressure, P  = 101.3 kPa. The temperature dependence of B -coefficients (d B /d T ), and viscosity B -coefficients of transfer (Δtr B ) of solutes from water to cosolute have also been estimated. These parameters have been discussed in terms of structure-making (kosmotropic) or -breaking (chaotropic) behavior of solutes.